Comparison of Japanese and Scottish Mother–Infant Intersubjectivity: Resonance of Timing, Anticipation, and Empathy During Feeding - Negayama, Koichi; Delafield-Butt, Jonathan T.; Momose, Keiko; Ishijima, Konomi; Kawahara, Noriko (Frontiers in Psychology, 2021)
Feeding involves communication between mothers and infants and requires precise synchrony in a special triadic relationship with the food. It is deeply related to their intersubjectivity. This study compared the development of mother-infant intersubjectivity through interactional synchrony in feeding between 11 Japanese and 10 Scottish mother-infant dyads, observed at 6 and 9 months by video. Japanese mothers were more deliberate in feeding at an earlier age, whereas Scottish mothers were significantly more coercive than Japanese mothers at an earlier age. Japanese mothers brought the spoon to infants with a pause to adjust the timing of insertion to match their infants’ readiness, whereas this pause was not observed in Scottish mothers. Isomorphic mouth opening between mothers and infants was observed. This empathic maternal display is an important element of intersubjectivity in infant feeding that differened between Scottish and Japanese mothers. Scottish mothers’ mouth opening always followed their infants’ mouth opening, but about half of Japanese mothers preceded their infants. Further, the mouths of Scottish infants and mothers opened almost at the same time as spoon insertion. In contrast, Japanese mothers’ mouth opening did not co-ocurr with the insertion but was close to spoon arrival, a subtle but important difference that allows for greater infant autonomy. The time structure of Scottish mother-infant interactions was simpler and more predictable at 9 months than in Japan, where the structure was more variable, likely due to a stronger regulation by Scottish mothers. In conclusion, Scottish mother-infant intersubjectivity is characterised as more maternally reactive and mother-centered, whereas Japanese mother-infant intersubjectivity is characterised as more maternally empathetic and infant-centered. Cultural differences in intersubjectivity during feeding between Japan and Scotland are further discussed in relation to triadic relationships and parenting styles.